Carcinogenic Ability of Schistosoma Haematobium Possibly through Oncogenic Mutation of KRAS Gene - Botelho, Mónica C. (2013)
Schistosoma haematobium is a parasitic flatworm that infects millions of people, mostly in the developing world, and is associated with high incidence of bladder cancer, although why is not clear. Previously, we have used CD-1 mice to show that Schistosoma haematobium total antigen (Sh) has a carcinogenic ability. Sh intravesically instillation induced the development of several urothelial lesions, namely nodular hyperplasia and dysplasia (LGIUN—Low Grade Intra-Urothelial Neoplasia) after 40 weeks of treatment. These results suggested that Sh induce urothelium malignization. Bladder carcinoma frequently harbours gene mutations that constitutively activate the receptor tyrosine kinase-Ras pathway for this reason we studied activating mutations in KRAS gene. Twenty percent of the bladders with dysplasia presented a KRAS mutation in codon 12 of exon 2. We concluded from these results that the parasite extract of S. haematobium has carcinogenic ability possibly through oncogenic mutation of KRAS gene.